L'iniziativa OpenDataNetwork, OpenData senza confini - Giannechini, Simone; Assfalg, Jurgen; Lorenzini, Chiara; Cipriani, Lorenzo (GEOmedia, 2013)
In the last few years, the Open Data movement has made a significant impact on the IT world by bringing the att ention to an unexploited value represented by the tremendous amount of data that was kept hidden behind the gates of the existing infrastructures, both in public administrations and in private companies. This value can be declined in many ways depending on the perspective of the observer since unprecedented possibilities to correlate different sources of data to mine hidden trends and patt erns, can all at a sudden provide innovative ways to evaluate and monitor events and real life situation. After the initial period of the widespread adoption of the Open Data principles, we are now experimenting a situation where the amount of data available as Open Data is becoming overwhelming as such the need for some kind of coordination effort between different Open Data infrastructures is needed in order to make the data easier to browse and to exploit. This is the goal of the Open Data Network initiative. The Open Data Network initiative aim at bringing together a certain number of Italian Public Administration with the goal of creating a standard infrastructure based on Open Source components suitable for the dissemination of data as Open Data. Moreover it aims at creating a network between each partner's node in order to ease the life of the end user as he will be allowed to access a central hub where all the information will be harvested, rather than having to deal with each single partner's infrastructure.